Loose fruit collector and instant packaging machine for palm oil industry / Akmal Lutfi Mohamad, Kamariah Md Isa and Ab Aziz Mohd Yusof - Mohamad, Akmal Lutfi; Md Isa, Kamariah; Mohd Yusof, Ab Aziz (School of Mechanical Engineering, 2023)
This project aims to help FELDA workers who have a hard time rearranging and packaging palm seeds when sending them to factories to make other products. Besides that, the palm seeds are small in size and are numerous to be picked up in a short period of time. The main objective for this project is to design and analyze the Loose fruit collector and its instant packaging procedure for it and also to fabricate a physical prototype of this project. Methods that are used in this project are rolling a collector roller along the earth’s floor and the roller will move along collecting the palm seeds in its way. Then, the sack can be tied and sent to the factories or sellers. In conclusion, this project is medium in cost and is environmentally safe. It does not use any source of power or electricity. It works fully through human effort. The materials used are also easy to find.